Studies on the lactic-fermentation of sugar apple (Annona squamosa L.) puree - Tien, Y. Y.; Ng, C. C.; Chang, C. C.; Tseng, W. S.; Kotwal, S.; Shyu, Y. T. (Journal of Food and Drug Analysis, 2005)
Sugar apple (Annona squamosa L.) is a fruit tree of economic importance in Taiwan, with the fruit primarily consumed fresh. Overproduction in recent years, coupled with short shelf life and other practical issues, make practical the research into uses for sugar apples in formats other than fresh. This study presents an exploration of lactic-fermented sugar apple products. The product has a unique sweet aroma and a test panel found its texture to be appealing. For this study, sugar apple puree was used as the substrate for fermentation using mixed starters in a ratio 1:1 or 1:1:1. The high total soluble solid nature (20.5 +/- 4.33 degrees Brix) of sugar apple puree as compared to that of mixed fruit juice (lower than 10 Brix) indicates its potential to be used in fermentation. Following fermentation, the properties and effects of different starter inoculations were recorded and discussed. Fermentation achieved a pH value of 3.8 after 60 hr. The performance of fermented product in the DPPH (alpha,alpha-diphenyl-beta- picrylhydrazyl) decreased from 92% to 78% after 48 hr, followed by a stationary state. Fermented sugar apple puree and fresh sugar apple juice blended in a ratio of 2:8 delivered the highest DPPH scavenging efficiency (88%) and iron chelating ability (49%). The relatively high values of these properties offer the potential for sugar apple juice to be further developed as a novel functional food. Such a development would surely help to ease recent overproduction problems.
Keywords: annonaceae; DPPH scavenging; Fermentation; Lactobacillus